(untitled) (International journal of artificial intelligence, 2025)
Today, modern information technologies and artificial intelligence systems play an important role in the early detection and treatment of vascular diseases. Artificial intelligence allows for the analysis of medical data, monitoring of heart activity, and automation of the diagnostic process. For example, machine learning and deep learning algorithms are widely used in the analysis of data obtained from equipment such as ECG (electrocardiogram), CT (computed tomography), and MRI (magnetic resonance imaging). Using artificial intelligence algorithms, changes in heart rhythm, circulatory disorders, and heart muscle activity are automatically analyzed. This greatly helps the doctor in early detection of the disease and making the correct diagnosis. It also helps to predict risk factors associated with the cardiovascular system. With the help of modern IT technologies, in particular mobile applications, digital stethoscopes, and online medical monitoring systems, the condition of patients is constantly monitored. This process allows medical staff to monitor the patient's heart activity remotely. Also, medical data is securely stored and transmitted to doctors for rapid analysis through cloud technologies. Algorithms created using artificial intelligence are widely used in processes such as monitoring heart rhythm, controlling blood pressure, and predicting the risk of heart attack. Cloud technologies and database systems also allow for real-time analysis of patient health data. In conclusion, modern information technologies and artificial intelligence create unparalleled opportunities for early detection of cardiovascular diseases, improving the quality of treatment, and digitizing medical services. In the future, this area will be further improved and will acquire significant scientific and practical importance in maintaining human health.